Analysis of The Creativity of Senior High School Students Through The C-R-E-A-T-E Learning Model - Wahyu, Wawan; Kusrijadi, Ali (FKIP Universitas Lampung, 2022)
This study aims to analyze students' creativity through the C-R-E-A-T-E learning model in a blended system. Voltaic Cell was chosen as the material studied because the process of making Voltaic Cells can support the development of students' creativity. The research method used was Design Based Research (DbR). The research instrument used was a creativity observation sheet according to William's creativity indicator and an assessment sheet for students' creative products which included three main skills: creating, investigating, and problem-solving skills. The results of this study indicate that the step-by-step C-R-E-A-T-E learning model implemented through a blended system supported by Google Classroom can develop students' creativity, both in terms of creative processes and creative products. It was shown from the observation results of students' creativity on the indicators of fluency, flexibility, elaboration, originality, and evaluation each included in the very good category. In addition, the average score of students' creative product assessment is also in the very good category. These results indicate that the learning model is feasible to be applied in learning as an effort to develop student creativity. Keywords: students’ creativity, the C-R-E-A-T-E model, senior high school. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1673-1682